Higher Frequency of Hospital-Acquired Infections but Similar In-Hospital Mortality Among Admissions With Alcoholic Hepatitis at Academic vs. Non-academic Centers - Waleed, Muhammad; Abdallah, Mohamed A.; Kuo, Yong-Fang; Arab, Juan P.; Wong, Robert; Singal, Ashwani K. (Frontiers in Physiology, 2020)
Background: Alcoholic hepatitis (AH) is a unique syndrome characterized by high short-term mortality. Impact of academic status of a hospital (urban and teaching) on outcomes in AH is unknown. Methods: NIS dataset (2006 -2014) on AH admissions stratified to academic center (AC) or non-academic center (NAC), and analyzed for in-hospital mortality (IHM), hospital resource use, length of stay (LOS) in days (d), and total charges (TC) in USD. Admission year was stratified to 2006-2008 (TMI), 2009-2011 (TM2), and 2012-2014 (TM3). Results: Of 62,136 AH admissions, proportion at AC increased from 46% in TM1 to 57% in TM3, Armitage trend, P<0.001. On logistic regression, TM3, younger age, black race, Medicaid and private insurance, and development of acute on chronic liver failure (ACLF) were associated with admission to an AC. Of 53,264 admissions propensity score matched for demographics, pay status, and disease severity, admissions to AC vs. NAC (26,622 each) were more likely to have liver disease complications (esophageal varices, ascites, and hepatic encephalopathy) and hospital acquired infections, especially C. difficile and ventilator associated pneumonia. Admissions to AC were more likely as transfer from outside hospital (1.6 vs. 1.3%) and seen by palliative care (4.8 vs. 3.3%), P<0.001. Use of endoscopy, dialysis, and mechanical ventilation were similar. With similar IHM comparing AC vs. NAC (7.7 vs. 7.8%, P=0.93), average LOS and number of procedures were higher at AC [7.7 vs. 7.1 d and 2.3 vs. 1.9 respectively, P<0.001] without difference on total charges [$52,821 vs. $52,067 USD, P=0.28]. On multivariable logistic regression model after controlling for demographics, ACLF grade, and calendar year, IHM was similar irrespective of academic status of the hospital, HR (95% CI): 1.01 (0.93-1.08, P=0.70). IHM decreased overtime, with ACLF as strongest predictor. A total of 63% and 22% were discharged to home and skilled nursing facility respectively, without differences on academic status of the hospital. Conclusions: Admissions with AH to AC compared to NAC have higher frequency of liver disease complications and hospital acquired infections, with longer duration of hospitalization. Prospective studies are needed to reduce hospital acquired infections among hospitalized patients with AH.